Canadian public libraries and search engines: barriers to visibility. Issue 5 (19th September 2016) - Dickinson, Zoe; Smit, Michael
Abstract : Purpose: The purpose of this paper is to examine the challenges presented by search engine visibility for public libraries. The paper outlines the results of a pilot study investigating search engine visibility in two Canadian public libraries. Design/methodology/approach: The study consists of semi-structured interviews with librarians from two multi-branch Canadian public library systems, combined with quantitative data provided by each library, as well as data obtained through site-specific searches in Google and Bing. Possible barriers to visibility are identified through thematic analysis of the interviews. Findings: The initial findings of this pilot study identify a complex combination of barriers to visibility on search engines, in the form of attitudes, policies, organizational structures, and technological difficulties. Research limitations/implications: This paper describes a small, preliminary pilot study. More research is needed before any firm conclusions can be reached. Practical implications: A review of the literature shows the increasing importance of search engine visibility for public libraries. By delving into the underlying issues which may be affecting libraries' progress on the issue, this paper may help inform libraries' decision-making processes and practices. Originality/value: There has been little original research investigating the reasons behind libraries' lack of visibility in search engine results pages. This paper provides insight into a previously unexplored area by exploring public libraries' relationships with search engines.